ANALISIS PERHITUNGAN MUATAN SEDIMEN (BED LOAD ) PADA MUARA SUNGAI LILIN KABUPATEN MUSI â€“BANYUASIN - Resnie Bella (Jurusan Teknik Sipil Fakultas Teknik Universitas Sriwijaya, 2014)
Lilin river has high economic valute. The function of this river as a connection between mainland. The purpose of this analysis is to find out the result of sedimentation happened in the edge Lilin river for sediment capacity bed load or basic of sediment. Sediment is pleces of materials, in general consist of rocks it is physically and chemically. Basic capacity (bed load) is particle that move in the base river. Situation of basic capacity always move, because of it along the base river always happen degradation and agradation process called as â€œalterasi base riverâ€ in research methodology use method dorect obseruation and the aspect is the buildup of sludge at Lilin river. The way to sediment is take the sample directly. The tools that used to take the sample were gauge, staff gauge, water dipper, wood and scoop. Analysis was used shear stress approach is Duboyâ€™s and Shieldâ€™s approach, then energy slope is Meyer Peter and Miillerâ€™s approach. Based on calculation bed load discharge by using 3 methods, there are Duboyâ€™s, Shiledâ€™s and Meyer Peter miillerâ€™s. Then the result of calculation discharge for 1 year at Lilin river by using Duboyâ€™s method has value qb was 6,83x105 (lb/thn/ft), Shieldâ€™s method has value qb was 8,33x10 5 (lb/thn/ft) and then qb by using Meyer-Peter and Miillerâ€™s was 4,99x10 7 (lb/thn/ft). for calculate the volume of sediment at edge Lilin river was value of qb by using Duboyâ€™s method was 267,42(lb/thn/ft), Shieldâ€™s method was 219,36 (lb/thn/ft), Meyer-Peter and Miillerâ€™s was 36603,26 (lb/thn/ft), then dredging could be done suitable with the volume of sediment that has been calculated. Key words : Sedimentation, The edge of river , Bed load